2016
DOI: 10.1152/ajpcell.00001.2016
|View full text |Cite
|
Sign up to set email alerts
|

High glucose promotes the migration of retinal pigment epithelial cells through increased oxidative stress and PEDF expression

Abstract: Defects in the outer blood-retinal barrier have significant impact on the pathogenesis of diabetic retinopathy and macular edema. However, the detailed mechanisms involved remain largely unknown. This is, in part, attributed to the lack of suitable animal and cell culture models, including those of mouse origin. We recently reported a method for the culture of retinal pigment epithelial (RPE) cells from wild-type and transgenic mice. The RPE cells are responsible for maintaining the integrity of the outer bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 80 publications
3
43
0
Order By: Relevance
“…According to previous reports investigating cell migration under high glucose condition, the effect of glucose on cell migration still remains controversial depending on the cell types [14, 44, 45]. Our data in this study revealed that high glucose stimulates hUCB-MSC migration with suppression of E-cadherin expression.…”
Section: Discussionsupporting
confidence: 64%
“…According to previous reports investigating cell migration under high glucose condition, the effect of glucose on cell migration still remains controversial depending on the cell types [14, 44, 45]. Our data in this study revealed that high glucose stimulates hUCB-MSC migration with suppression of E-cadherin expression.…”
Section: Discussionsupporting
confidence: 64%
“…Most researchers agree that one of the early events in DR is the dysfunction of RPE, affecting the retina [8]. In DR, RPE dysfunction is consequence of hyperglycemia, leading to a dysregulation on different protein expression, which, in turn, contributes to oxidative stress and, eventually, angiogenesis [9,10].…”
Section: Retinal Pigment Epithelium and Diabetic Retinopathymentioning
confidence: 99%
“…The RPE cells also selectively transport of metabolites, ions, nutrients and water between retina and choriocapillaris (Strauss 2005). The dysfunction of RPE is related to retinal degeneration and irreversible vision loss, and is the first event in DR (Yang et al 2006; Farnoodian et al 2016; Simao et al 2017; Xie et al 2014). In rodent diabetic models, hyperglycemia induced the dysfunction, even death of RPE cells which led to the development of DR (Xia and Rizzolo 2017).…”
Section: Introductionmentioning
confidence: 99%